Identification and Experimental Validation of the Prognostic Significance and Immunological Correlation of Glycosylation-Related Signature and ST6GALNAC4 in Hepatocellular Carcinoma - Dai T; Li J; Liang RB; Yu H; Lu X; Wang G (Journal of Hepatocellular Carcinoma, 2023)
Tianxing Dai,1,2,* Jing Li,3,* Run-Bin Liang,1,* Haoyuan Yu,2 Xu Lu,2 Guoying Wang1,2 1Department of Hepatobiliary Surgery, The First Affiliated Hospital of Guangzhou Medical University, Guangzhou, 510120, People’s Republic of China; 2Department of Hepatic Surgery and Liver Transplant Program, The Third Affiliated Hospital of Sun Yat-sen University, Guangzhou, 510630, People’s Republic of China; 3Department of Gastroenterology, The Second Affiliated Hospital of Guangzhou Medical University, Guangzhou, 510260, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guoying Wang, Department of Hepatobiliary Surgery, The First Affiliated Hospital of Guangzhou Medical University, 151 Yanjiangxi Road, Guangzhou, 510120, People’s Republic of China, Tel +86-20-83062703, Fax +86-20-83395651, Email wanggy3@126.comPurpose: Glycosylation has been demonstrated to be involved in tumorigenesis, progression, and immunoregulation, and to present specific profiles in different tumors. In this study, we aimed to explore the specific glycosylation-related gene (GRG) signature and its potential immunological roles and prognostic implications in hepatocellular carcinoma (HCC).Patients and Methods: The GRG expression profile was defined using the transcriptome data from The Cancer Genome Atlas and Gene Expression Omnibus. Univariate and the least absolute shrinkage and selection operator Cox analyses were performed to develop a GRG-based risk score model. A nomogram was subsequently established and validated. Its correlation with cancer immune microenvironment and drug susceptibility was further analyzed. The role and immunological correlation of ST6GALNAC4 were further experimentally validated at the tissue and cellular levels in HCC.Results: A total of 87 GRGs were identified to be significantly dysregulated in HCC, and a novel risk score model was constructed using eight critical GRGs, which demonstrated superior prognostic discrimination and predictive power in both training and validation groups. High risk scores in HCC patients were associated with lower OS. The model was also identified as an independent risk factor for HCC, and a novel nomogram was subsequently constructed and validated. Notably, significant correlations were found in risk scores with immune cells infiltration, tumor immunophenotyping, immune checkpoint genes’ expression, and sensitivities to multiple drugs. Furthermore, we validated in local HCC samples that ST6GALNAC4 was significantly upregulated and its knockdown significantly inhibited the tumor proliferation, migration and invasion ability and affected the expression of immune checkpoints on hepatoma cells.Conclusion: We identified a novel GRG-based model which showed significant prognostic and immunological correlations in HCC, and the oncogenic role of ST6GALNAC4 has been validated and may serve as a potential drug target.Keywords: hepatocellular carcinoma, glycosylation, ST6GALNAC4, gene signature, prognosis, immune checkpoint